Prevalence of periodontitis among the adolescents aged 15-18 years in Mangalore City: An epidemiological and microbiological study - K Pallavi Nanaiah; D V Nagarathna; Nandini Manjunath (Wolters Kluwer Medknow Publications, 2013)
Background: Periodontitis is a group of inflammatory diseases affecting the supporting tissues of the tooth. Both aggressive periodontitis (AP) and chronic periodontitis (CP) have a multifactorial etiology, with dental plaque as the initiating factor. However, the initiation and progression of periodontitis are influenced by other factors including microbiologic, social and behavioral and systemic and genetic factors. The prevalence of periodontal diseases varies in different regions of the world according to the definition of periodontitis and the study population, and there are indications that they may be more prevalent in developing than in developed countries. Materials and Methods: A cross-sectional study was conducted among the adolescents of 15-18 years of age in Mangalore City. One thousand one hundred students aged 15-18 years were selected for the study from the schools and colleges in Mangalore City using a convenient sampling method. The prevalence of AP and CP were assessed in the study using a community periodontal index. Students who were diagnosed clinically and radiographically were subjected to microbiological examination to confirm AP. Results: A high prevalence of gingivitis and periodontitis was found in students belonging to the lower socioeconomic status group compared with the higher socioeconomic groups, which were associated with poor oral hygiene habits. The prevalence of AP was found to be 0.36% and that of CP was found to be 1.5%. Conclusion: Oral diseases have a significant impact on the social and psychological aspects of an individual's life. Exposure to risk factors, such as age, low socio-economic status, poor education, low dental care utilization, poor oral hygiene levels, smoking, psychosocial stress and genetic factors are significantly associated with an increased risk of periodontitis among adolescents. Although genetic factors play a major role in periodontitis, the treatment outcome will still be influenced by environmental and behavioral factors.